Media and Myth-Making in Contemporary Philippines, Indonesia, and Malaysia - Salazar, Joseph T. (Plaridel Journal of Communication, Media, and Society; Vol 6 No 1 (2009): Media and Folklore, 2011)
The study explores the connections between different media practices in three Southeast Asian countries in three different decades. These practices employ the biggest myth perpetuated in this age of information and technology, namely, nationalism. The changes affecting Southeast Asia from the 1980s to the present have been nothing but dramatic. Many of these changes reflect the blurring of the region’s once exclusive national borders into a consolidated mass of cultural and economic practices reeking of global capitalism benefiting the new middle class. Surprisingly, the production of images and texts by media pertaining to nationalist sentiments has intensified and has become the center of many developmental efforts in the region. At the same time, the same practices have also managed to alienate local customs, traditions and cultures that do not comply with the mythological image of a modern Southeast Asia.